Cytotoxicity evaluation of Clinacanthus nutans through dimethylthiazol diphenyltetrazolium bromide and neutral red uptake assays - La Ongthong Vajrabhaya (2018)
© 2016 European Journal of Dentistry. Objectives: The aim of this study was to compare the results of dimethylthiazol diphenyltetrazolium bromide (MTT) and neutral red uptake (NRU) assays of Clinacanthus nutans cytotoxicity. Materials and Methods: Mouse fibroblast (L929) cells were exposed to 0.01%, 0.1%, 0.25%, and 0.5% (W/V) C. nutans in a 96-cluster-well-culture plate for 24 h. The cell viability after exposure to C. nutans was determined by MTT and NRU assays in separate tissue culture plates. The two assays were compared through an intra-class correlation coefficient (ICC) analysis. Results: No significant differences in cytotoxicity were noted between the two assays (P > 0.05). The ICC values for agreement between two assays for the negative and positive control groups and C. nutans concentrations of 0.01%, 0.1%, 0.25%, and 0.5% were 0.84, 0.83, 0.77, 0.68, 0.74, and 0.71, respectively. Conclusion: In general, the MTT and NRU assays performed similarly, exhibiting moderate to good correlation for the evaluation of the cytotoxicity of C. nutans.